Reverse The Name of The Certificate of Title To The Estate Unilaterally Without The Knowledge of The Other Heirs - Aprilian Herdiana, Nabilla Rizki; Neltje Saly, Jeane (Green Publisher Indonesia, 2023)
Property Rights are the descending rights, strongest and fullest that a person can have over land. Property rights can be transferred and transferred to other parties because a legal event occurs due to the death of a person so that the property left behind passes to the heirs and legal actions occur if there is a transfer of rights from the rights holder or his heirs to the new rights holder. If there is an abandoned land certificate, the land certificate is also transferred. A certificate is a proof of land rights to guarantee legal certainty. How is the legal settlement of the reverse action of the title certificate to the estate unilaterally without the knowledge of the other heirs. The research method used in writing tesis in the form of a normative juridical approach method. Specifications The research used in this study is analytical descriptive research. The types and sources of data used by the author are secondary data types, data obtained through data sources of civil law literature studies and primary legal materials, secondary legal materials, tertiary legal materials. Data collection techniques are obtained through literature studies and interviews. The method of analysis in thesis research is in the form of Qualitative Juridical. The results of the research on the reverse name of the title certificate to the heirs unilaterally without the knowledge of other heirs; The first provides legal protection for heirs who have full rights related to the act of unilaterally reversing the name of the title certificate to the estate without the knowledge of the other heirs is that each heir has the right to file a lawsuit through the Court to fight for his heir rights as per Article 834 of the Civil Code. Secondly, the legal settlement of the reverse action of the name of the title certificate to the estate unilaterally without the knowledge of the other heirs is to file a lawsuit through the court institution if the court decision has been issued that has obtained permanent legal force, the title certificate contains defects law in its issuance and declared invalid and unlawful